Can dams affect the trophic structure of ichthyofauna? A long-term effects in the Neotropical region - Lima, Felipe P. De; Nobile, André B.; Freitas-souza, Diogo; Carvalho, Edmir D.; Vidotto-magnoni, Ana P. (Fundação Zoobotânica do Rio Grande do Sul, 2018)
ABSTRACT Dams are considered an important source of modification upon the structure of aquatic communities and their reflexes are diverse on the fish fauna. Although there are several hydroelectric power plants in Brazil, the long-term effects on feeding activity of ichthyofauna are unknown. Thus, this study aimed to investigate the long-term effects of an old reservoir (fifty years) on the trophic dynamics of fish fauna. The diet of 20 fish species was analyzed, identifying 37 food items belonging to six trophic categories, which enable to create six trophic groups. The results found here suggests that throughout the creation of a reservoir, the trophic structure of the fish assemblages tend to reach trophic homeostasis, in which the fish community will be capable of exploring the most available food resources being maintained primarily by the items placed in the categories organic matter and fragments of fish and vegetal.

RESUMO As barragens são consideradas uma importante fonte de modificação na estrutura das comunidades aquáticas e seus reflexos são diversos na fauna de peixes. Embora existam várias usinas hidrelétricas no Brasil, os efeitos a longo prazo sobre a atividade de alimentação da ictiofauna são desconhecidos. Assim, este estudo teve como objetivo investigar os efeitos a longo prazo de um antigo reservatório (50 anos) sobre a dinâmica trófica da ictiofauna. A dieta de 20 espécies de peixes foi analisada, identificando 37 itens alimentares pertencentes a seis categorias tróficas, que possibilitaram a criação de seis grupos tróficos. Os resultados aqui encontrados sugerem que, ao longo da formação de um reservatório, a estrutura trófica das assembleias de peixes tende a atingir a homeostase trófica, na qual a comunidade de peixes será capaz de explorar os recursos alimentares mais disponíveis sendo mantidos principalmente pelos itens colocados nas categorias matéria orgânica e fragmentos de peixes e vegetais.
Podem barragens afetar a estrutura trófica da ictiofauna? Efeitos de longo prazo na Região Neotropical
Keywords: Feeding ecology; old dam; trophic stabilization; resource availability; fishes; Ecologia alimentar; reservatório antigo; estabilização trófica; disponibilidade de recursos; peixes